Effect of C6H8O7 Concentration on Silica Extraction of Rice Husk, Rice Husk Ash and Mixture of Rice Husk With Rice Husk Ash Via Acid Leaching Process - Syahirah Mohd Zarib, Noratiqah; Abdullah, Shahrulazam; ., . (International Journal of Engineering and Technology, 2018)
Rice husk and rice husk ash are wastes found in agricultural industry. Rice husk contains over 70% of organic silica. Silica is used in industries such as functional filler for paints, plastics, rubber while silica sand is used in water filtration and agriculture. The organic silica could be extracted through various methods such as sol-gel method, purification and hydrothermal heat carrier. The focus of this paper is to analyse the effect of acid treatment of silica extraction of rice husk and rice husk ash. Parameters such as concentration of acid and weight percentage used in the mixture of rice husk and rice husk ash during organic leaching method were also compared. In this paper, citric acid (C6H8O7) was used for production of silica from rice husk and rice husk ash. Samples were characterized using Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) and Energy Dispersive X-Ray Spectroscopy (EDEX). The result indicates that highest percentage silica of rice husk, rice husk ash and mixture between rice husk and rice husk ash after leaching has an amorphous structure.
Keywords: silica; rice husk; rice husk ash; inorganic acid; agriculture waste